Preparation process of high-wear-resistance composite coating applied to hob of shield tunneling machine

By using ultrasonic rolling treatment and high vacuum magnetron sputtering film deposition technology on the shield machine hob, a high wear-resistant composite coating with self-lubricating function is prepared, which solves the problem of insufficient coating bonding force in the prior art, and achieves the high wear resistance and strong impact toughness of the hob.

CN119876879APending Publication Date: 2025-04-25JIMEI UNIV

Patent Information

Application Number
CN202510190323.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

When the prior art improves the wear resistance of the hob of the shield machine, the difference in mechanical properties between the coating and the substrate leads to insufficient binding force, which cannot be maintained stable under heavy load environments, resulting in the coating falling off and the inability to effectively improve rock breaking ability.

Method used

The microtextured surface of the hob was constructed by ultrasonic rolling treatment, and the chromium intermediate layer and tungsten carbide intermediate layer were prepared by deposition of high vacuum magnetron sputtering film, and finally covered with chromium-doped diamond-like film to form a high wear-resistant composite coating.

Benefits of technology

It significantly improves the mechanical bond between the coating and the substrate, optimizes the tribological properties and corrosion resistance, enhances the wear resistance and impact toughness of the hob, extends the service life and reduces engineering costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876879A_ABST
    Figure CN119876879A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation process of a high-wear-resistance composite coating applied to a shield tunneling machine hob, and belongs to the technical field of surface modification.The preparation process comprises the following steps that S1, ultrasonic rolling treatment is conducted on the surface of a hob base body, a hob surface gradient structure is built, and meanwhile a micro-texture is constructed; s2, high-vacuum magnetron sputtering thin film deposition is conducted on the surface of the hob with the surface microtexture prepared in the step S1, and a middle layer of a composite coating is coated; and S3, performing true high-altitude magnetron sputtering film deposition on the surface of the hob deposited with the middle layer in the step S2, and coating a chromium-doped diamond-like carbon film of a composite coating. According to the preparation process of the high-wear-resistance composite coating applied to the shield tunneling machine hob, on the basis of constructing a hob foundation and preparing a surface micro-texture, the high-wear-resistance and high-toughness composite gradient coating with a self-lubricating function is prepared, so that the hob has high wear resistance and high impact toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of surface modification, and in particular to a preparation process of a high-wear-resistant composite coating applied to a shield machine cutter. Background Art

[0002] With the rapid economic development, the demand for urban underground tunnel development, national highways and railways and other infrastructure construction projects is increasing. In the process of rock tunnel excavation, shield machines are widely used due to their high efficiency, economy and environmental protection. As a key component of the shield machine, the cutter needs to continuously withstand huge pressure, impact force and frequent friction during excavation. The tunnel excavation conditions are complex, and the cutter is subjected to huge contact stress when in contact with granite with different degrees of weathering, which accelerates the wear of the cutter. A large amount of engineering data from tunnels shows that failures caused by normal wear of the cutter account for 88% of the total number of tool failures. Therefore, constructing a reasonable gradient structure of the cutter and improving its wear resistance in excavation in harsh environments are key issues that need to be solved. Further extending the service life of the cutter and reducing engineering costs have practical and guiding significance.

[0003] At present, the main ways to improve the wear resistance of shield machine hobs are tool structure design, surface modification and coating. For example, patent CN117821708A uses surface technologies such as modulated heat treatment and laser impact modification to construct a gradient structure on the hob surface to improve the hardness, wear resistance and life of the hob. Chinese patent application CN117187497A uses carburizing and nitriding heat treatment processes and ultrasonic impact modification to construct a gradient structure cutter ring to improve the hardness, wear resistance and life of the hob. However, these technologies are limited to the improvement of the material itself, which only improves its wear resistance to a limited extent. In contrast, the coating can break through the limitations of the cutter ring substrate. Chinese patent application CN110802311B uses laser additive technology to prepare a coating on the cutter ring surface to improve the hardness, wear resistance and excavation life of the shield machine. Chinese patent application CN114214693B uses laser texture treatment on the substrate surface and laser cladding to prepare a coating, which improves the impact resistance and high wear resistance of the cutter ring surface. However, these patents do not focus on the difference in mechanical properties between the coating and the substrate, and cannot guarantee the bonding strength between the coating and the substrate. They are very easy to fall off under heavy load conditions and cannot actually improve the rock-breaking ability of the shield machine cutter.

[0004] In summary, it can be concluded that there are the following problems in improving the wear resistance of shield machine cutters: only focusing on the modification of the material itself, although it can save a lot of economic costs, but the improvement in wear resistance is limited; preparing a coating on the surface of the cutter ring, the coating can have a thermal expansion coefficient matching the substrate and good high-temperature phase stability, which can effectively improve the wear resistance of the cutter, but the mechanical difference between the coating and the cutter ring substrate cannot guarantee the bonding strength under heavy load. Summary of the invention

[0005] The purpose of the present invention is to provide a process for preparing a high wear-resistant composite coating for use in shield machine cutters. On the basis of constructing a cutter base and preparing a surface microtexture, a highly wear-resistant and tough composite gradient coating with self-lubricating function is prepared, so that the cutter has both high wear resistance and strong impact toughness properties.

[0006] To achieve the above object, the present invention provides a process for preparing a high wear-resistant composite coating for a shield machine cutter, comprising the following steps: S1. Perform ultrasonic rolling treatment on the surface of the hob substrate to create a gradient structure on the hob surface and construct micro-texture; S2, performing high vacuum magnetron sputtering thin film deposition on the surface of the hob with surface micro-texture prepared in S1, and applying an intermediate layer of the composite coating; S3. Performing vacuum high-altitude magnetron sputtering thin film deposition on the surface of the hob on which the intermediate layer has been deposited in S2, and applying a composite coating of chromium-doped diamond-like carbon thin film.

[0007] Preferably, the specific operation of S1 is: S11. Use ethanol to ultrasonically clean the hob substrate to ensure that the sample surface is smooth and free of impurities, and then dry it with compressed air; S12, subjecting the roller cutter prepared in S11 to ultrasonic rolling treatment to construct a gradient structure and surface microtexture.

[0008] Preferably, the ultrasonic rolling parameters in S12 are: static pressure of 1000-1500N, amplitude of 5-10μ, frequency of 25-30KHz, feed speed of 500-1000mm / min, and processing times of once; The gradient structure is: the surface residual stress is -1050~-1100MPa, and the depth of the affected layer is 0.5mm~0.6mm; The surface microtexture is as follows: microtexture depth is 1.5-2.0 μm, microtexture width is 150-200 μm, adjacent microtexture spacing is 100-150 μm, and surface roughness is 400-600 nm.

[0009] Preferably, the specific operation of S2 is: S21, performing high vacuum magnetron sputtering thin film deposition on the hob with the prepared surface microtexture, and depositing a chromium intermediate layer using a chromium target in a DC mode; S22, subjecting the roller with the chromium intermediate layer deposited thereon to high vacuum magnetron sputtering film deposition, and using a carbon target and a tungsten target to deposit a tungsten carbide intermediate layer.

[0010] Preferably, when performing high vacuum magnetron sputtering film deposition in S21, the deposition environment is less than 1.3×10 -5In a vacuum environment with a pressure of 100 bar, the hob surface is bombarded with an argon ion flow of 20~40ccm for 20~40min at a bias voltage of -60~-40V. The cathode current is 0.8~1.0A, and the input power of the inductively coupled plasma etcher is 800~1000W.

[0011] Preferably, when high vacuum magnetron sputtering thin film deposition is performed in S22, the deposition environment is less than 1.3×10 -5 In a vacuum environment with a pressure of 0.6 bar, under a bias voltage of -60~-40V, the hob surface is bombarded with an argon ion flow of 20~40ccm for 20~40min, the cathode current is 0.8~1.0A, the input power of the inductively coupled plasma etcher is 800~1000W, the carbon target concentration is 99.99%, the size is 2 inches, and the tungsten target concentration is 99.99%, the size is 2 inches.

[0012] Preferably, the specific operation of S3 is: subjecting the deposited tungsten carbide roller intermediate layer to high vacuum magnetron sputtering thin film deposition, reducing the cathode current to 0.4~0.5A, increasing the bias voltage to -150~-130V, introducing 4~6sccm acetylene input flow into the system, ensuring that the current is stable at 500~800nm / H during the deposition process, and preparing a chromium-doped diamond-like film.

[0013] Preferably, the thickness of the chromium intermediate layer is 0.6-0.7 mm.

[0014] Preferably, the thickness of the tungsten carbide intermediate layer is 0.6-0.7 mm.

[0015] Preferably, the thickness of the diamond film is 1-1.5 mm, and the diamond-like film is a chromium-doped hydrogenated diamond-like film.

[0016] Therefore, the present invention adopts the above-mentioned high wear-resistant composite coating preparation process for shield machine roller cutter, which has the following beneficial effects: (1) The surface micro-texture prepared by ultrasonic rolling can effectively accommodate abrasive particles, reduce the direct scratching and cutting effect of abrasive particles on the coating surface, and thus reduce the wear rate of the coating; a microscopic concave-convex structure is formed on the surface of the hob substrate, which increases the contact area between the coating and the substrate and significantly improves the mechanical bonding force between the coating and the substrate.

[0017] (2) The ultrasonic rolling microtexture and the chromium-doped diamond-like composite coating work synergistically to optimize the tribological properties between the cutter and the rock and soil medium; the addition of chromium further improves the corrosion resistance of the composite coating. Chromium can form a dense passivation film on the coating surface, which can effectively resist the erosion of corrosive ions, reduce the risk of cutter failure caused by corrosion, and improve the reliability and durability of shield machine cutters in complex geological environments.

[0018] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 It is a flow chart of preparing surface micro-texture and composite coating of Example 1 of a high wear-resistant composite coating preparation process for a shield machine roller cutter of the present invention; Figure 2 It is a schematic diagram of the structure of a high wear-resistant composite coating applied to a shield machine roller cutter according to an embodiment of the present invention; Figure 3 It is an enlarged view of A of an embodiment of a process for preparing a high wear-resistant composite coating applied to a shield machine cutter of the present invention; Figure 4 This is a cross-sectional schematic diagram of a high-wear-resistant composite coating structure of a shield machine cutter according to Example 1 of a process for preparing a high-wear-resistant composite coating for a shield machine cutter.

[0020] Reference numerals 1. Hob substrate; 2. Microtexture; 3. Chromium intermediate layer; 4. Tungsten carbide intermediate layer; 5. Chromium-doped diamond-like carbon film. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below through the accompanying drawings and embodiments.

[0022] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.

[0023] The present invention provides a process for preparing a high wear-resistant composite coating for a shield machine cutter, wherein the high wear-resistant composite coating for a shield machine cutter is as follows: Figure 2 and Figure 3 As shown, from bottom to top, there are: a hob substrate 1, a surface micro-texture 2, a chromium intermediate layer 3, a tungsten carbide intermediate layer 4 and a chromium-doped diamond-like film 5, and the preparation method thereof comprises the following steps: S1, ultrasonic rolling treatment is performed on the surface of the hob substrate 1 to create a gradient structure on the hob surface and construct a micro texture 2. The specific operation is as follows: S11, ultrasonically clean the hob substrate 1 with ethanol to ensure that the sample surface is smooth and free of impurities, and dry it with compressed air; S12. The roller prepared in S11 is subjected to ultrasonic rolling treatment to construct a gradient structure and surface micro-texture 2, wherein the ultrasonic rolling parameters are: static pressure of 1000~1500N, amplitude of 5~10μ, frequency of 25~30KHz, feed speed of 500~1000mm / min, and processing times of once; the gradient structure is: surface residual stress of -1050~-1100MPa, and depth of affected layer of 0.5mm~0.6mm; surface micro-texture 2 is: micro-texture depth of 1.5~2.0μm, micro-texture width of 150~200μm, spacing between adjacent micro-textures of 100-150μm, and surface roughness of 400-600nm.

[0024] S2, performing high vacuum magnetron sputtering thin film deposition on the surface of the hob with surface micro-texture 2 prepared in S1, and applying an intermediate layer of the composite coating, the specific operation is as follows: S21, the hob with the surface micro-texture 2 prepared is subjected to high vacuum magnetron sputtering film deposition, and the deposition environment is less than 1.3×10 -5 In a vacuum environment with a pressure of bar, the hob surface is bombarded with an argon ion flow of 20~40ccm for 20~40min at a bias voltage of -60~-40V. The cathode current is 0.8~1.0A, the input power of the inductively coupled plasma etcher is 800~1000W, and the chromium intermediate layer 3 is deposited using a chromium target in a DC mode. The thickness of the chromium intermediate layer 3 is 0.6~0.7mm.

[0025] S22, the hob on which the chromium intermediate layer 3 is deposited is subjected to high vacuum magnetron sputtering film deposition, and the deposition environment is less than 1.3×10 -5 In a vacuum environment with a pressure of 1 bar, under a bias voltage of -60~-40V, the hob surface is bombarded with an argon ion flow of 20~40ccm for 20~40min, the cathode current is 0.8~1.0A, the input power of the inductively coupled plasma etcher is 800~1000W, and a 2-inch carbon target with a concentration of 99.99% and a 2-inch tungsten target with a concentration of 99.99% are used to deposit a tungsten carbide intermediate layer 4, and the thickness of the tungsten carbide intermediate layer 4 is 0.6~0.7mm.

[0026] S3, performing true high altitude magnetron sputtering film deposition on the hob surface where the intermediate layer has been deposited in S2, and applying a composite coating of chromium-doped diamond-like carbon film 5, the specific operation is as follows: The hob intermediate layer with deposited tungsten carbide is subjected to high vacuum magnetron sputtering film deposition, the cathode current is reduced to 0.4~0.5A, the bias voltage is increased to -150~-130V, and the system introduces 4~6sccm acetylene input flow. During the deposition process, the current is kept stable at 500~800nm / H to prepare a chromium-doped diamond-like film 5. The thickness of the diamond film is 1~1.5mm. The diamond-like film uses a chromium-doped hydrogenated diamond-like film.

[0027] Example 1 like Figure 1 As shown, the present invention provides a process for preparing a high wear-resistant composite coating applied to a shield machine cutter, comprising the following steps: (1) Preparation of surface microtexture 2: like Figure 4 As shown, the hob substrate 1 uses a 19-inch medium carbon steel base hob to prepare a high wear-resistant composite coating, and the surface micro-texture 2 with a depth of 1.6μm, a width of 150μm, and an adjacent spacing of 150μm is prepared on the surface of the 19-inch medium carbon steel base hob using ultrasonic rolling technology, and the surface roughness is increased to 500nm. The ultrasonic rolling static pressure is 1500N, the amplitude is 6μ, the frequency is 28kHz, the feed speed is 1000mm / min, and the number of processing times is once.

[0028] (2) Preparation of chromium intermediate layer 3 The chromium intermediate layer 3 was prepared on the surface of the 19-inch medium carbon steel substrate hob micro-texture 2 by high vacuum magnetron sputtering film deposition. The deposition environment was less than 1.3×10 -5 In a vacuum environment with a pressure of 100 bar, the hob surface was bombarded with an argon ion flow of 30 ccm for 30 min at a bias voltage of -50 V. The cathode current was 0.8 A, the input power of the inductively coupled plasma etcher was 1000 W, and a chromium intermediate layer 3 with a thickness of 0.6-0.7 mm was prepared using a chromium target in the DC mode.

[0029] (3) Preparation of tungsten carbide intermediate layer 4 The tungsten carbide layer 4 was prepared on the surface of the 19-inch medium carbon steel substrate hob micro-texture 2 by high vacuum magnetron sputtering film deposition. The deposition environment was less than 1.3×10 -5 In a vacuum environment with a pressure of 100 bar, the hob surface was bombarded with an argon ion flow of 30 ccm for 30 min at a bias voltage of −50 V. The cathode current was 0.8 A, the input power of the inductively coupled plasma etcher was 1000 W, and a tungsten carbide intermediate layer 4 with a thickness of 0.6-0.7 mm was deposited using a 2-inch carbon target with a concentration of 99.99% and a 2-inch tungsten target with a concentration of 99.99%.

[0030] (4) Preparation of chromium-doped diamond-like carbon films 5 A diamond-like carbon film 5 was prepared on the surface of a 19-inch medium carbon steel substrate hob micro-texture 2 using high vacuum magnetron sputtering film deposition. The cathode current was reduced to 0.4A, the bias voltage was increased to -150V, and an acetylene input flow of 5.0sccm was introduced into the system. During the deposition process, the current was kept stable at 700nm / H to prepare a chromium-doped diamond-like film 5 with a thickness of 1~1.5mm.

[0031] Comparative Example 1 This comparative example provides a process for preparing a non-textured coating applied to a shield machine cutter, and the steps are as follows: (1) Preparation of cutter ring blank The hob substrate adopts a 19-inch medium carbon steel base hob made of medium carbon steel, and specifically uses the same batch of materials as in Example 1. The blank is prepared by hot forging process, and then subjected to rough grinding and other processing.

[0032] (2) Surface modification by ultrasonic rolling The ultrasonic rolling technology is used to modify the surface of the 19-inch medium carbon steel substrate hob. The ultrasonic rolling static pressure is 1500N, the amplitude is 6μ, the frequency is 28kHz, the feed speed is 1000mm / min, the processing times are once, and the coverage rate is full coverage.

[0033] Comparative Example 2 This comparative example provides a non-textured composite coating process applied to a shield machine cutter, comprising the following steps: (1) Preparation of cutter ring blank The hob substrate adopts a 19-inch medium carbon steel base hob made of medium carbon steel, and specifically uses the same batch of materials as in Example 1. The blank is prepared by hot forging process, and then subjected to rough grinding and other processing.

[0034] (2) Preparation of chromium intermediate layer The chromium intermediate layer was prepared by high vacuum magnetron sputtering film deposition on the micro-textured surface of a 19-inch medium carbon steel substrate. The deposition environment was less than 1.3×10 -5 In a vacuum environment with a pressure of 100 bar, the hob surface was bombarded with an argon ion flow of 30 ccm for 30 min at a bias voltage of -50 V. The cathode current was 0.8 A, the input power of the inductively coupled plasma etcher was 1000 W, and a chromium intermediate layer with a thickness of 0.6-0.7 mm was prepared using a chromium target in DC mode.

[0035] (3) Preparation of tungsten carbide intermediate layer As shown in the figure, a tungsten carbide intermediate layer was prepared on the micro-textured surface of a 19-inch medium carbon steel substrate using high vacuum magnetron sputtering film deposition. The deposition environment was less than 1.3×10 -5 In a vacuum environment with a pressure of 100 bar, the hob surface was bombarded with an argon ion flow of 30 ccm for 30 minutes at a bias voltage of -50 V. The cathode current was 0.8 A, the input power of the inductively coupled plasma etcher was 1000 W, and a 2-inch carbon target with a concentration of 99.99% and a 2-inch tungsten target with a concentration of 99.99% were used to deposit a tungsten carbide intermediate layer with a thickness of 0.6~0.7 mm.

[0036] (4) Preparation of undoped diamond-like carbon films Diamond-like carbon film was prepared on the micro-textured surface of a 19-inch medium carbon steel substrate using high vacuum magnetron sputtering film deposition. The cathode current was reduced to 0.4A, the bias voltage was increased to -150V, and an acetylene input flow of 5.0sccm was introduced into the system. During the deposition process, the current was kept stable at 700nm / H. A 2-inch carbon target with a concentration of 99.99% was used to prepare an undoped diamond-like film with a thickness of 1~1.5mm.

[0037] The different wear-resistant shield machine cutters prepared in Example 1 and Comparative Examples 1-2 were subjected to a 1-hour friction and wear test, and the results are as follows: Table 1 Friction and wear test results

[0038] The experimental results show that the cutter ring treated in Example 1 has good wear resistance in a 1-hour friction and wear test. The self-lubricating function of the coating surface significantly reduces the friction coefficient. After surface micro-texture pretreatment, the bonding force is significantly improved without cracking. Comparative Example 1 only modifies the surface, the wear resistance is limited, and the friction coefficient is relatively high. Comparative Example 2 does not perform surface texture pretreatment, the coating bonding force is reduced, and the lack of chromium doping leads to large internal stress in the coating and reduced impact toughness. It shows good wear resistance in the early stage of friction, but the coating breaks and the friction coefficient increases in the later stage of friction, indicating that the use of a high wear-resistant composite coating preparation process for shield machine rollers provided in this application can significantly improve wear resistance and increase the tunneling life of the shield machine.

[0039] Therefore, the present invention adopts the above-mentioned high wear-resistant composite coating preparation process applied to shield machine cutter. On the basis of constructing the cutter base and preparing the surface micro-texture, a high wear-resistant and tough composite gradient coating with self-lubricating function is prepared, so that the cutter has both high wear resistance and strong impact toughness properties.

[0040] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A process for preparing a high wear-resistant composite coating for a shield machine cutter, characterized in that: The following steps are involved: S1. Perform ultrasonic rolling treatment on the surface of the hob substrate to create a gradient structure on the hob surface and construct micro-texture; S2, performing high vacuum magnetron sputtering thin film deposition on the surface of the hob with surface micro-texture prepared in S1, and applying an intermediate layer of the composite coating; S3. Performing vacuum high-altitude magnetron sputtering thin film deposition on the surface of the hob on which the intermediate layer has been deposited in S2, and applying a composite coating of chromium-doped diamond-like carbon thin film.

2. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 1, characterized in that: The specific operations of S1 are: S11. Use ethanol to ultrasonically clean the hob substrate to ensure that the sample surface is smooth and free of impurities, and then dry it with compressed air; S12, subjecting the roller cutter prepared in S11 to ultrasonic rolling treatment to construct a gradient structure and surface microtexture.

3. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 2, characterized in that: The ultrasonic rolling parameters in S12 are: static pressure of 1000~1500N, amplitude of 5~10μ, frequency of 25~30KHz, feed speed of 500~1000mm / min, and processing times of once; The gradient structure is: the surface residual stress is -1050~-1100MPa, and the depth of the affected layer is 0.5mm~0.6mm; The surface microtexture is as follows: microtexture depth is 1.5-2.0 μm, microtexture width is 150-200 μm, adjacent microtexture spacing is 100-150 μm, and surface roughness is 400-600 nm.

4. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 1, characterized in that: The specific operations of S2 are: S21, performing high vacuum magnetron sputtering thin film deposition on the hob with the prepared surface microtexture, and depositing a chromium intermediate layer using a chromium target in a DC mode; S22, subjecting the roller with the chromium intermediate layer deposited thereon to high vacuum magnetron sputtering film deposition, and using a carbon target and a tungsten target to deposit a tungsten carbide intermediate layer.

5. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 4, characterized in that: When high vacuum magnetron sputtering thin film deposition is performed in S21, the deposition environment is less than 1.3×10 -5 In a vacuum environment with a pressure of 100 bar, the hob surface is bombarded with an argon ion flow of 20~40ccm for 20~40min at a bias voltage of -60~-40V. The cathode current is 0.8~1.0A, and the input power of the inductively coupled plasma etcher is 800~1000W.

6. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 4, characterized in that: When high vacuum magnetron sputtering thin film deposition is performed in S22, the deposition environment is less than 1.3×10 -5 In a vacuum environment with a pressure of 0.6 bar, under a bias voltage of -60~-40V, the hob surface is bombarded with an argon ion flow of 20~40ccm for 20~40min, the cathode current is 0.8~1.0A, the input power of the inductively coupled plasma etcher is 800~1000W, the carbon target concentration is 99.99%, the size is 2 inches, and the tungsten target concentration is 99.99%, the size is 2 inches.

7. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 1, characterized in that: The specific operation of S3 is: to carry out high vacuum magnetron sputtering thin film deposition on the hob intermediate layer with deposited tungsten carbide, the cathode current is reduced to 0.4~0.5A, the bias voltage is increased to -150~-130V, and the system introduces 4~6sccm acetylene input flow. During the deposition process, the current is kept stable at 500~800nm / H to prepare chromium-doped diamond-like carbon film.

8. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 4, characterized in that: The thickness of the chromium intermediate layer is 0.6~0.7mm.

9. A process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 4, characterized in that: The thickness of the tungsten carbide intermediate layer is 0.6~0.7mm.

10. The process for preparing a high wear-resistant composite coating for a shield machine cutter according to claim 7, characterized in that: The thickness of the diamond-like carbon film is 1-1.5 mm, and the diamond-like carbon film adopts a chromium-doped hydrogenated diamond-like film.

Citation Information

Patent Citations

  • A method for wear-resistant and impact-resistant treatment of tunnel boring machine cutterhead rings

    CN110802311B

  • A surface machining method for tunnel boring machine cutterheads

    CN114214693B

  • Composite modification process of high-toughness wear-resistant hob cutter ring for tunneling of shield tunneling machine

    CN117187497A

  • Surface layer structure of high-wear-resistance shield tunneling machine hob and preparation process of surface layer structure

    CN117821708A

Cited By

  • IC soaking sheet surface micro-texture forming method and device

    CN120866768A